Tipping points in adaptation to urban flooding under climate change and urban growth: The case of the Dhaka megacity. (December 2018) - Ahmed, Farhana; Moors, Eddy; Khan, M. Shah Alam; Warner, Jeroen; Terwisscha van Scheltinga, Catharien
Highlights: Tipping points may occur in the physical system due to unplanned urban development. Zone specific strategies are required for spatial planning based adaptation. Unplanned urbanization with climate change leads to adaptation tipping points. Apparently, climate change affects flooding more than the unplanned development. Abstract: Envisioning the future city as the outcome of planned development, several master and strategic plans for Dhaka were prepared. However, these plans, do not adequately address the well-known and combined effects of climate change and unplanned urbanization on urban flooding. Additionally, the spatial planning component is missing in adaptation planning, which broadly concentrates on the climate change. Long-term adaptation strategies should consider both the temporal and spatial extent of flooding. Uncertainties in climate change and urbanization will induce planning failure beyond the Adaptation Tipping Point for flooding exceeding the thresholds of the bio-physical system or the acceptable limits of societal preference. In this paper, a shift is proposed from the current planning practice of single-dimensional 'Predict and Act' towards a more resilience-based 'Monitor and Adapt' approach. It is prudent to visualize the effects of urbanization and climate change and translate them into strategies for improved adaptation based spatial planning. Here, Dhaka's exposure to floods under different climate change and urban (planned and unplanned) development scenarios is assessed based on acceptable thresholds obtained from plans (top-down defined) and stakeholders (bottom-up perspectives). The scale of effects of these two drivers on urban flooding is exhibited through the zone differentiated flooding extent. While apparently the effect of climate change on flooding is greater than that of unplanned urban developments, both play an important role in instigating tipping points and intensifying risks.